2017
DOI: 10.1016/j.jpainsymman.2016.12.348
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making Regarding the Place of End-of-Life Cancer Care: The Burden on Bereaved Families and Related Factors

Abstract: Decision making regarding the place of EOL care was recalled as burdensome for family decision makers. An early decision-making process that incorporates sharing patients' and family members' values that are relevant to the desired place of EOL care is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The impact of such challenges is consistent with studies demonstrating decisional burden of FC in cases of uncertainty about patient's wishes and conflicting needs, e.g. regarding the place of care and death [13,15]. For example, a study on FC who made a surrogate decision about the place of end-of-life care showed that FC reported significantly more burden when the decision was not concordant with the patient's wishes [15].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The impact of such challenges is consistent with studies demonstrating decisional burden of FC in cases of uncertainty about patient's wishes and conflicting needs, e.g. regarding the place of care and death [13,15]. For example, a study on FC who made a surrogate decision about the place of end-of-life care showed that FC reported significantly more burden when the decision was not concordant with the patient's wishes [15].…”
Section: Discussionsupporting
confidence: 77%
“…However, studies suggest that at least one-third of FC face emotional pressure and decisional burden associated with doubt and regret months or even years afterwards, which could lead to depression and stronger grief [8,13]. High caregiver burden has been reported specifically in case of substitute decision-making responsibilities, uncertainty about the patient's wishes and values, and conflicting wishes regarding the place of death [13][14][15]. In the context of palliative and end-of-life care, FC may encounter manifold morally distressing problems or ethical dilemmas.…”
Section: Introductionmentioning
confidence: 99%
“…However, family's paternalistic decisions may not consider the patient's values or result in reasonable decisions respecting the self-determination right of the patient (25). In addition, family members could suffer from decisional burden and experience depression and grief (26,27) due to surrogate decision making. The present study results showed that building an environment in which patients and family have open discussions and encouraging LST discussions with patients and family can be strategies to reduce family-related barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Family members play an important role in end-of-life cancer decisionmaking (Laryionava et al, 2018;Yamamoto et al, 2017). Family members in Asian countries have often adopted the role of decisionmakers on behalf of patients due to the family-centered cultural tradition (Li, 2013;Mo et al, 2012;Yamamoto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Family members play an important role in end-of-life cancer decisionmaking (Laryionava et al, 2018;Yamamoto et al, 2017). Family members in Asian countries have often adopted the role of decisionmakers on behalf of patients due to the family-centered cultural tradition (Li, 2013;Mo et al, 2012;Yamamoto et al, 2017). Such a familial decision-making pattern in Asian countries has been observed, even for competent patients, and more frequently for those approaching death (Kim, 2015;Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%